2011
DOI: 10.3340/jkns.2011.50.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Vein of Galen Aneurysmal Malformation : Endovascular Management of 6 Cases in a Single Institute

Abstract: Objective : The aim of this study was to analyze the treatment outcome of patients with vein of Galen aneurysmal malformations (VGM). Methods : Clinical and angiographic data of six consecutive patients with VGM were retrospectively reviewed. VGMs were angiographically classified by Yasargil's method. Treatment outcomes were evaluated. Results : Mean age at initial treatment was 4.4±5.7 months. Angiographic types of VGMs were type II in two patients and type III in four. Three patients had cardiac symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The literature search identified a total of 34 studies, [3][4][5][6][7][8][9][12][13][14][15]17,20,[22][23][24][25]28,30,[32][33][34][35][36][37][38][39][40][41][42]45,46,50,51 which included 667 patients whose VGAMs were treated by endovascular embolization (Fig. 1).…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%
“…The literature search identified a total of 34 studies, [3][4][5][6][7][8][9][12][13][14][15]17,20,[22][23][24][25]28,30,[32][33][34][35][36][37][38][39][40][41][42]45,46,50,51 which included 667 patients whose VGAMs were treated by endovascular embolization (Fig. 1).…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%
“…V ein of Galen arteriovenous malformations (VOGMs) are shunts that form in utero between the choroidal arteries and the precursor of the vein of Galen, the median prosencephalic vein of Markowski. [1][2][3] Current prevalence estimates of VOGM are quite low, often cited at Ͻ1 of 25,000 deliveries. 4,5 A number of studies have shown that the natural history of VOGMs is very poor, with many patients succumbing to complications related to congestive heart failure (CHF), hydrocephalus, and brain parenchymal injury.…”
mentioning
confidence: 99%
“…Endovascular embolization of VOGMs has emerged as a standard of care in this patient population; however, long-term outcomes after endovascular embolization, as well as predictors of good neurologic outcomes, are still poorly understood. [2][3][4] Thus, to assess the status of endovascular treatment for VOGMs, we performed a systematic review and meta-analysis with an emphasis on determining factors associated with good neurologic outcome in this patient population.…”
mentioning
confidence: 99%
“…Patient clinical outcomes were analyzed in the 19 studies in which spontaneous thromboses occurred (see online supplementary table S6) 4 20 21 25 26 42–55. Online supplementary table S7 presents the clinical outcome of patients with spontaneous thromboses for various age groups.…”
Section: Resultsmentioning
confidence: 99%